Understanding National Insights of Junior High School Students in The Digital Era - Faridatul Lailiyah; Armawati Hidayati; Tamam Syaifuddin; Srisetyowati (International Journal of Geography, Social, and Multicultural Education, 2023)
The digital era is a signal of the rapid flow of information obtained by the younger generation, especially junior high school/equivalent students. The impact that is starting to be felt is the spread of acts of terrorism, crimes that lead to acts of separatism that adorn the news today. This can happen due to the erosion of the values ??contained in national insight. The aim of this research is to measure how far the younger generation, especially junior high school/equivalent students, understand and understand national insight. The method used is a survey with a descriptive quantitative approach supported by the SPSS application by conducting a Validity Test and Reliability Test. The results of the research show that junior high school students in the digital era have an understanding of national insight in the average or sufficient category with Mean=66.12, supported by a validity test, there is a Pearson correlation of 0.373 sig=0.015 (significant/valid), and a reliability test of 0.802 ( reliable), so it is important to follow up in increasing the understanding of national insight of junior high school students in the digital era, especially in Citizenship subjects